ANALISIS KUALITATIF DAN KUANTITATIF CEMARAN LOGAM BERAT TIMBAL (Pb) DAN KADMIUM (Cd) PADA PRODUK KOSMETIK PENSIL ALIS MENGGUNAKANSPEKTROFOTOMETER SERAPAN ATOM (SSA) - Arifiyana, Djamilah; Fernanda, MA Hanny Ferry (Journal of Research and Technology, 2018)
The aim of this study was to identify and determine the heavy metal content of lead (Pb) and cadmium (Cd) towards eyebrow pencil registered and not registered by the Food and Drug Supervisory Agency (BPOM). This research was conducted in several markets in Surabaya. Twelve eyebrow pencil items were investigated for lead (Pb) and cadmium (Cd). Simple reagents, included HCl, NaOH, KI, Na2S2O3 and NH4OH were used to identify the presence of these heavy metal first. The study results showed that samples of eyebrow pencil registered and unregistered by BPOM RI after being tested turned out to contain lead and cadmium in a range of 1.092-5,834 mg/kg and 0,054-0.243 mg/kg, respectively. The content is still within what is required based on the regulations of BPOM RI, < 20 mg/kg for lead content and < 5 mg/kg for cadmium content. In short, all the sample of eyebrow pencil contained lead (Pb) and cadmium (Cd) within what is required based on the regulations of BPOM RI.